Androgens and female sexuality - Łukasiewicz, Monika; Lew-Starowicz, Zbigniew; Bińkowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2009)
The sexual response in women is considered to be multidimensional, involving hormonal, physiological, relational, emotional, and psychological parameters. It is also suggested that reduced level of testosterone in postmenopausal women is associated with loss of libido, decreased sexual activity, diminished feeling of physical well-being and fatigue. The transdermal testosterone patch is an effective treatment for hypoactive sexual disorder in surgically postmenopausal women. Testosterone is generally well tolerated. However, prospectively collected long-term studies are needed to estimate the risk of breast cancer and cardiovascular diseases.